EVALUATING THE INFLUENCE OF USER-GENERATED CONTENT IN DIGITAL MARKETING CAMPAIGNS: A STUDY OF BRAND ADVOCACY - Ali Khalaf Mohammed Alsukaini (Scholars Digest Publishing, 2024)
In the field of digital marketing, this study paper investigates the relationship between user-generated content (UGC) and brand advocacy. The research uses a quantitative approach to looking at customer feedback in order to look at four key areas: how user-generated content is seen, how much people engage with it, how this affects company endorsement, and how digital platforms help people engage with user-generated content, a look at The data is that most people like user-generated content (UGC), but the amount of engagement varies from one digital site to another. Hypothesis testing shows that there is a statistically significant relationship between good user-generated content (UGC) and brand advocacy. This shows how important user-generated content is in building brand loyalty, and data shows that user-generated content (UGC) has a significant impact on how people think about and talk about a brand. But how well user-generated content works depends on the digital platform and the type of interaction that occurs. The study says that intentionally using user-generated content (UGC) in digital marketing can increase brand loyalty. He stresses how important it is to be real and create strategies that suit each platform.
Keywords: User-Generated Content, Brand Advocacy, Digital Marketing Strategies, Consumer Engagement, Social Media Impact, Marketing Communication, Quantitative Analysis.